Research and innovation policies in the new global economy an international comparative analysis - Larédo, P. (Philippe); Mustar, Philippe (New horizons in the economics of innovation, 2001)
This work re-evaluates national systems of innovation. Analytical descriptions of the national system combine with historical perspectives. Topics include the changing rationale for government laboratories and the proficiency of government to adopt to rapid changes in innovation systems.